Branched chain α‐ketoacid dehydrogenase kinase 111–130, a T cell epitope that induces both autoimmune myocarditis and hepatitis in A/J mice. Issue 4 (9th June 2017) - Krishnan, Bharathi; Massilamany, Chandirasegaran; Basavalingappa, Rakesh H.; Gangaplara, Arunakumar; Kang, Guobin; Li, Qingsheng; Uzal, Francisco A.; Strande, Jennifer L.; Delhon, Gustavo A.; Riethoven, Jean‐Jack; Steffen, David; Reddy, Jay
Abstract: Introduction: Organ‐specific autoimmune diseases are believed to result from immune responses generated against self‐antigens specific to each organ. However, when such responses target antigens expressed promiscuously in multiple tissues, then the immune‐mediated damage may be wide spread. Methods: In this report, we describe a mitochondrial protein, branched chain α‐ketoacid dehydrogenase kinase (BCKDk ) that can act as a target autoantigen in the development of autoimmune inflammatory reactions in both heart and liver. Results: We demonstrate that BCKDk protein contains at least nine immunodominant epitopes, three of which, BCKDk 71–90, BCKDk 111–130 and BCKDk 141–160, were found to induce varying degrees of myocarditis in immunized mice. One of these, BCKDk 111–130, could also induce hepatitis without affecting lungs, kidneys, skeletal muscles, and brain. In immunogenicity testing, all three peptides induced antigen‐specific T cell responses, as verified by proliferation assay and/or major histocompatibility complex class II/IA k dextramer staining. Finally, the disease‐inducing abilities of BCKDk peptides were correlated with the production of interferon‐γ, and the activated T cells could transfer disease to naive recipients. Conclusions: The disease induced by BCKDk peptides could serve as a useful model to study the autoimmune events of inflammatory heart and liver diseases. Abstract : BCKDk, a mitochondrial protein, was found to contains multiple epitopes that induce cardiac autoimmunity, and one epitope can also induce hepatitis. Pathogenicity of BCKDk peptides was associated with T cell responses that produce mainly IFN‐γ, and the antigen‐sensitized T cells can transfer disease to naive recipients.